DERİN MİKOZLARIN EPİDEMİYOLOJİSİ; ANTİFUNGAL PROFİLAKSİ İLE İLGİLİ GÖRÜŞLER VE ANTİFUNGAL DUYARLILIK DENEYLERİ - KANTARCIOĞLU, A. Serda; YÜCEL, Ayhan (Cerrahpaşa Medical Journal, 2014)
Background.- Invasive mycoses are deep seated fungal infections involving mucosa and penetrate host tissues. This term actually covers “subcutaneous” and “systemic mycoses”. The virulence factors of the fungus and host immune status play role in the pathogenesis of invasive mycoses. Fungus that possess high virulence causes diseases in immunocompetent individuals. Invazive fungal infections due to low virulence opportunistic fungi are associated with increased morbidity and mortality in immunocompromised patients. Some of these pathogens show resistance to currently available antifungal agents. Understanding the risk factors associated with deep fungal infection may facilitate identification of high risk patients and guide appropriate initiation of antifungal therapy.This paper briefly reviews current knowledge of the changing epidemiology for invasive mycoses, controversial considerations about antifungal prophylaxis, and current status of antifungal susceptibility tests.